Automation of measurements of photoelectric parameters of high-impedance semiconductor films - Dzundza, B.S.; Prokopiv, V.V.; Mazur, T.M.; Yurchyshyn, L.D. (Physics and Chemistry of Solid State, 2018)
A method of measuring electrical conductivity and photoconductivity of semiconductor films with high electrical resistance has been described. The electric circuit has been presented and the computer program has been developed. That provides automation of measurements, registration and primary processing of data with possibility of plotting time dependences for preliminary analysis of experimental data during measurement.